Comparison by Age of the Local Interferon Response to SARS-CoV-2 Suggests a Role for IFN-ε and -ω - Pierangeli, Alessandra; Gentile, Massimo; Oliveto, Giuseppe; Frasca, Federica; Sorrentino, Leonardo; Matera, Luigi; Nenna, Raffaella; Viscido, Agnese; Fracella, Matteo; Petrarca, Laura; D’Ettorre, Gabriella; Ceccarelli, Giancarlo; et al. (Frontiers in Immunology, 2022)
Children generally develop a mild disease after SARS-CoV-2 infection whereas older adults are at risk of developing severe COVID-19. Recent transcriptomic analysis showed pre-activated innate immunity in children, resulting in a more effective anti-SARS-CoV-2 response upon infection. To further characterize age-related differences, we studied type I and III interferon (IFN) response in SARS-CoV-2 infected and non-infected individuals of different ages. Specifically, levels of expression of type I (IFN-α, -β, -ε and -ω), type III (IFN-λ1, -λ2 and -λ3) IFNs and of the IFN-stimulated genes, ISG15 and ISG56 were quantified in nasopharyngeal cells from diagnostic swabs. Basal transcription of type I/III IFN genes was highest among children and decreased with age. Among SARS-CoV-2-infected individuals, only IFN-ε and -ω levels were significantly higher in children and young adults whereas ISGs were overexpressed in infected adults. The occurrence of symptoms in children and the need for hospitalization in adults were associated to higher transcription of several IFN genes. Starting from a pre-activated transcription level, the expression of type I and III IFNs was not highly up-regulated in children upon SARS-CoV-2 infection; young adults activated IFNs’ transcription at intermediate levels whereas older adults were characterized by higher ISGs and lower IFN-ε and -ω relative expression levels. Overall, our findings contribute to recognize components of a protective IFN response as a function of age, in the context of SARS-CoV-2 infection.